Torque teno mini virus driven childhood acute promyelocytic leukemia: The third case report and sequence analysis - Chen, Xue; Wang, Fang; Zhou, Xiaosu; Zhang, Yang; Cao, Panxiang; Ma, Xiaoli; Yuan, Lili; Fang, Jiancheng; Liu, Mingyue; Liu, Ming; Chen, Jiaqi; Chen, Qihui; et al. (Frontiers in Oncology, 2022)
In this manuscript, we report torque teno mini virus (TTMV) as a cause of acute promyelocytic leukemia (APL) lacking PML::RARA in a 3-year-old boy. Astolfi et al. firstly identified partial integration of the TTMV genome into RARA intron 2, which resulted in in-frame TTMV::RARA fusion in two APL-like pediatric cases without PML::RARA in November 2021. This fascinating report identified an unexpected exogenous genetic cause of APL and could be of great importance for diagnosing and managing APL. Here we report the third childhood APL-like case caused by TTMV integration and investigate the location and structure of the integrated TTMV sequence. These findings suggest TTMV::RARA is a recurrent cause of APL lacking PML::RARA. Considering the widespread prevalence of TTMV in the population, more TTMV::RARA positive APL-like cases might remain to be identified. Establishing a bioinformatic analysis strategy optimized for the highly variable TTMV genome sequence may facilitate the identification of TTMV::RARA by whole transcript sequencing. An effective PCR protocol to identify TTMV::RARA based on a profound analysis of the conservation of TTMV segments in the fusion transcript is also expected. Also, further investigation is needed to elucidate the oncogenic mechanisms of TTMV integration and the clinical features of TTMV::RARA positive patients.